2021
DOI: 10.21037/apm-21-1840
|View full text |Cite
|
Sign up to set email alerts
|

Ballistocardiography to identify high left atrial pressure in patients with heart failure

Abstract: Background: Due to a high prevalence and morbidity rate, heart failure (HF) constitutes an immense economic burden on the global health care system. An increase in left atrial pressure (LAP) precedes the occurrence of any HF symptoms. In this study, we applied a novel non-invasive method of ballistocardiography (BCG) to extract early diastolic ventricular vibration waves [the BCG-B3 index, which corresponds to the third heart sound (S3) at the end of the rapid filling phase of diastole]. This study evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…evaluated the predictive value of the BCG‐B3 index, measured with a high‐precision fibre‐optic sensor on the back, to detect an estimated increased left atrial pressure derived from echo E/e′ ratio in HF patients, which is generally considered an early predictor of acute HF decompensation. In line with other studies, this study showed that BCG measurements are responsive to changes in left atrial pressure 18 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…evaluated the predictive value of the BCG‐B3 index, measured with a high‐precision fibre‐optic sensor on the back, to detect an estimated increased left atrial pressure derived from echo E/e′ ratio in HF patients, which is generally considered an early predictor of acute HF decompensation. In line with other studies, this study showed that BCG measurements are responsive to changes in left atrial pressure 18 …”
Section: Discussionsupporting
confidence: 93%
“…In line with other studies, this study showed that BCG measurements are responsive to changes in left atrial pressure. 18 The present study proved that the KCG is able to detect changes in fluid status between the decompensated and recompensated state in HF patients. From a physiological point of view, these results can be explained by changes in blood flow velocities during the active and passive filling phases of the cardiac cycle.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations